Emerging roles for noncoding RNAs in female sex steroids and reproductive disease. (1st December 2020) - Zhang, Runju; Wesevich, Victoria; Chen, Zhaojuan; Zhang, Dan; Kallen, Amanda N.
Abstract: The "central dogma" of molecular biology, that is, that DNA blueprints encode messenger RNAs which are destined for translation into protein, has been challenged in recent decades. In actuality, a significant portion of the genome encodes transcripts that are transcribed into functional RNA. These noncoding RNAs (ncRNAs), which are not transcribed into protein, play critical roles in a wide variety of biological processes. A growing body of evidence derived from mouse models and human data demonstrates that ncRNAs are dysregulated in various reproductive pathologies, and that their expression is essential for female gametogenesis and fertility. Yet in many instances it is unclear how dysregulation of ncRNA expression leads to a disease process. In this review, we highlight new observations regarding the roles of ncRNAs in the pathogenesis of disordered female steroid hormone production and disease, with an emphasis on long noncoding RNAs (lncRNAs) and microRNAs (miRNAs). We will focus our discussion in the context of three ovarian disorders which are characterized in part by altered steroid hormone biology – diminished ovarian reserve, premature ovarian insufficiency, and polycystic ovary syndrome. We will also discuss the limitations and challenges faced in studying noncoding RNAs and sex steroid hormone production. An enhanced understanding of the role of ncRNAs in sex hormone regulatory networks is essential in order to advance the development of potential diagnostic markers and therapeutic targets for diseases, including those in reproductive health. Our deepened understanding of ncRNAs has the potential to uncover new applications and therapies; however, in many cases, the next steps will involve distinguishing critical ncRNAs from those which are merely changing in response to a particular disease state, or which are altogether unrelated to disease pathophysiology. Highlights: Noncoding RNAs are shown to regulate sex steroid biosynthesis and secretion. Updated review on the role of noncoding RNA in disordered sex steroid production. Their functions are further explored within the context of prevalent reproductive diseases.